2021
DOI: 10.3390/ma14237242
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Geometrical Accuracy of Thin-Walled Elements Made of Different Aluminum Alloys

Abstract: In modern constructions, especially aircraft, the aim is to minimize the weight of the components used. This necessitates the use of innovative construction materials, or the production of these parts with ever-decreasing wall thicknesses. To simplify assembly and improve strength properties, so-called structural elements are being used in the form of monolithic elements, which are replacing the assemblies of parts joined by, for example, riveting. These structures often have a complex, thin-walled geometry wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The obtained lower wall deformation after High Speed Cutting resulted from lower value of cutting force in comparison to HPC and convent ional machining. Such considerations were presented in [47].…”
Section: Resultsmentioning
confidence: 99%
“…The obtained lower wall deformation after High Speed Cutting resulted from lower value of cutting force in comparison to HPC and convent ional machining. Such considerations were presented in [47].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also shown that higher geometric accuracy of the manufactured elements is related to an increase in cutting speed. High cutting speeds are recommended to minimize distortion of thin-walled components [ 25 ]. The third tested parameter, the depth of cut, did not have a significant effect on the deformation and surface roughness of produced parts [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The research on machining thin-walled structures sometimes provides contradictory results, because there are also studies showing that the thickness of an aluminum alloy element does not significantly affect the 2D and 3D surface roughness parameters [ 3 ]. Due to the accuracy of workmanship and deformation of thin-walled elements made of aluminum alloys, it is recommended to use carbide tools or tools with PCD blades [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low forces that occur during brushing processing allow the application to thin-walled parts where low stiffness causes problems in the machining [ 26 , 27 ]. The use of appropriate machining strategies reduces the risk of deformation of thin-wall workpieces.…”
Section: Introductionmentioning
confidence: 99%